2013
DOI: 10.1177/0081246313508348
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to caregiver involvement in a child safety intervention in South Africa

Abstract: Injuries are a global threat to children's health and are disproportionately prevalent in Sub-Saharan Africa. Despite the rates of childhood injuries, research into prevention and the community and family conditions required for such interventions have been largely under-researched. This article reviews international work highlighting caregiver involvement in the implementation of interventions in a number of sectors, including the health, education, and safety domains. This work, based largely on experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The lowest male-to-female ratio was observed in young children (0–4 years), with high differentials observed in older children and young adult men. Injury vulnerability in South African boys has been associated with differing temperament, impulsivity, higher activity levels and less restraint of exploratory behaviour by parents 21 24 25. The current study specifically identifies young adult men (20–34 years) as a high-risk group for fatal drowning.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The lowest male-to-female ratio was observed in young children (0–4 years), with high differentials observed in older children and young adult men. Injury vulnerability in South African boys has been associated with differing temperament, impulsivity, higher activity levels and less restraint of exploratory behaviour by parents 21 24 25. The current study specifically identifies young adult men (20–34 years) as a high-risk group for fatal drowning.…”
Section: Discussionmentioning
confidence: 94%
“…However, the distribution of risk factors observed in this age group suggests that improved supervision presents a key area for drowning prevention efforts in the Western Cape. In particular, fatal drowning incidents in this age group frequently occurred in the early evening on weekdays, when care givers are likely to be preoccupied with caring for multiple children and performing household chores21 and were more likely to occur in swimming pools, baths and other water in and around the home. Increased awareness of the importance of adequate supervision at home may significantly reduce drowning risk in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…The UCS was implemented in a South African community that is under-resourced and faced with a range of considerable obstacles when trying to access public health and social services [ 22 , 23 ]. Throughout the implementation of the UCS the authors observed that the community faced multiple demands and priorities related to employment, basic municipal services, welfare, health and family safety.…”
Section: Influences On the Implementation Of The Ucsmentioning
confidence: 99%
“…These families and breadwinners often have precarious employment with little control over work schedules, which may include weekends. Other breadwinners may have more than one job, leaving minimal time for involvement in community activities [ 22 , 24 ]. Over the course of the UCS, the authors also noted sporadic episodes of tension and violence in the community, including gang-related violence, and the violence associated with the subsequent funerals of gang members, which disrupted several of the intervention events.…”
Section: Influences On the Implementation Of The Ucsmentioning
confidence: 99%
See 1 more Smart Citation